The role of spiritual mindset and gender in small business entrepreneurial success - Margaça, Clara; Sánchez-García, Jose C.; Cardella, Giuseppina Maria; Hernández-Sánchez, Brizeida R. (Frontiers in Psychology, 2022)
Introduction Spirituality can be understood as a capital based on individual capabilities created by the application of intrinsic spiritual values, in order to use and develop human potential. The literature points out that spiritual capital increasingly influences and motivates entrepreneurs. Methods In this paper, we investigate whether spirituality has a mediating role between psychological resilience, optimism and entrepreneurial success, and verify the gender differences. Our hypotheses are quantitatively tested on a sample of 233 micro and small Portuguese business owners during the pandemic crisis. Results The main findings highlight that, while optimism and psychological resilience present a positive and significant relationship with entrepreneurial success in both genders, spirituality only impacts female entrepreneurial success. Discussion Our study theoretically and empirically shows that the psychological resources and spirituality can be incorporated into new or existing programs designed to provide entrepreneurs with information on coping skills and how to engage in positive reorientation and reappraisal. In so doing, it improves the knowledge of the importance of psychological resources for the micro and small business’ recoverability during the pandemic, which is deeply rooted in the entrepreneurial ability to excel during adversity.